The use of prepositions among Malay adult ESL learners - Sudhakaran, Beena (European Centre for Research Training and Development (ECRTD), 2015)
One predicament facing an educationist is whether grammar should be taught formally, or allowed to be naturally acquired. A protracted case study was carried out on seven Malay students from the International Islamic University Malaysia to determine the extent to which students acquired English prepositions in the naturalistic setting. Data from students’ interviews and presentations were collected initially, and subsequently at six monthly intervals over three years. An analysis of students’ use of prepositions was carried out. Results showed that although errors persist, most subjects showed improvements in their use of prepositions. These findings imply that grammar should be taught in a way that is compatible with the natural processes of acquisition. Language instructors should also be equipped with special skills to be able to teach prepositions. Learners should also be developmentally ready to acquire prepositions, and changes have to be made in the curriculum for instruction of prepositions.